Nepali English or Other Varieties of English: Perspectives from English Language Teachers in Nepal (Journal of NELTA, 2022)
This qualitative content analysis article aims at exploring the perspectives of English language teachers on Nepali English (NE). I purposively selected six college level English language teachers from Sunsari and Morang districts and collected the required data through a semi-structured interview. The study reveals that NE has emerged in Nepal as a result of mother tongue inﬂuence, nativization of English to local contexts, and exposure from the non-native teachers during the second language acquisition process, and it is practically more appropriate than other varieties of English in Nepal. All the research participants favour NE as it is more intelligible and easier to teach and learn than the other varieties of English, promotes Nepali identity, boosts conﬁdence, reduces anxiety, and helps to resist the hegemony of British English (BE) or American English (AE). They, however, believe that more research and discourse on NE, its codiﬁ cation and standardization, and power (political, economic, and ideological) are necessary for bringing NE into concrete form. These perspectives from the English language teachers on NE pave the ground for appropriating English language policies, English language curriculum, textbooks, and pedagogy in Nepal, and rethinking the traditional treatment of errors.